Ciało w labiryncie znaczeń. O granicach cielesności w "Pamiętniku znalezionym w wannie" Stanisława Lema - Kucharczyk, Łukasz (Colloquia Litteraria, 2020)
The article deals with ways of displaying motifs of corporeality and problems that are evoked by the Stanisław Lem’s “Memoirs Found in a Bathub”. It begins with the description of the novel as an epistemological metaphor that reproduces the universal picture of the 20th century science, then the current genological reception of the work is quoted, which allows the passage to its description as a work containing elements of French noveau roman. The text also deals with the role of subjectivism in Lem’s narrative strategy. The body described in the novel is an automatic, artificial body, serving as a mask. The whole reality of the novel’s internal world is interpretive, but it still shows the hero’s pursuit of truth, the desire to know it. The aesthetics of the body in the text is compared to the body aesthetics of Gombrowicz, its social functions and philosophical context are also described, based on the reflection of Maurice Merleau-Ponty and Emmanuel Lévinas.